Brittle cornea syndrome: Disease-causing mutations in ZNF469 and two novel variants identified in a patient followed for 26 years - Skalicka, Pavlina; Porter, Louise F; Brejchova, Kristyna; Malinka, Frantisek; Dudakova, Lubica; Liskova, Petra (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2020)
AIMS: Brittle cornea syndrome (BCS) is a rare autosomal recessive disorder. The aim of this study was to review ZNF469 mutations associated with BCS type 1 to date and to describe an additional case of Czech/Polish background. METHODS: Whole genome sequencing was undertaken to identify the molecular genetic cause of disease in the proband. Sequence variants in ZNF469 previously reported as BCS type 1-causing were searched in the literature, manually curated and aligned to the reference sequence NM_001127464.2. RESULTS: The proband has been reviewed since childhood with progressive myopia and hearing loss. Aged 13 years had been diagnosed with Stickler syndrome. Aged 16.5 years, he developed acute hydrops in the left eye managed by corneal transplantation. At the age of 26, he experienced right corneal rupture after blunt trauma, also managed by grafting. He had a number of secondary complications and despite regular follow-up and timely management, the right eye became totally blind and the left eye had light perception at the last follow-up visit, aged 42. He was found to be a compound heterozygote for two novel mutations c.1705C>T; p.(Gln569*) and c.1402_1411del; p.(Pro468Alafs*31) in ZNF469. In total 22 disease-causing variants in ZNF469 have been identified, mainly in consanguineous families or endogamous populations. Only four probands, including the case described in the current study, harboured compound heterozygous mutations. CONCLUSION: BCS occurs very rarely in outbred populations which may cause diagnostic errors due to poor awareness of the disease. Investigation into the underlying molecular genetic cause in patients with connective tissue disorders may lead to a re-evaluation of their clinical diagnosis.
Keywords: Corneal Perforation; brittle cornea syndrome; Diagnostic Errors; blindness; myopie; nemoci pojiva; glaukom; penetrating keratoplasty; reoperace; Heterozygote; ZNF469; perforace rohovky; Retinal Detachment; nestabilita kloubu; corneal rupture; abnormality očí; Trabeculectomy; mužské pohlaví; Keratoplasty, Penetrating; odchlípení sítnice; Skin Abnormalities; Adult; Transcription Factors; trabekulektomie; Glaucoma; Reoperation; keratoplastika perforující; Eye Abnormalities; Hearing Loss, Sensorineural; Joint Instability; Corneal Edema; transkripční faktory; Connective Tissue Diseases; artritida; Arthritis; Humans; percepční nedoslýchavost; chybná diagnóza; kožní abnormality; edém rohovky; Myopia; Vitrectomy; dospělí; vitrektomie; deafness; lidé; Male; heterozygot